Genome-resolved characterization of candidate thermotolerance traits and predicted protein conformational behavior in Calditerricola during hyperthermophilic composting of organic wastes - Xu Li; Zhengnan Zhu; Youzhao Wang; Yanping Zhang; Xiaoyan Dang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Feng Ma; Liying Hao; Tong Zhu (Bioresource Technology, 2026)

Diversity of Diaporthe species associated with post-harvest decay on kiwifruit in China - Lu Feng; Yang Lin; Chao Li; Jiatao Xie; Jiasen Cheng; Bo Li; Tao Chen; Daohong Jiang; Yanping Fu (Fungal Biology, 2026)

Spatial heterogeneity of humic acids- and nitrate-driven anaerobic oxidation of methane mediated by ANME-2d in paddy soils - Yanan Bai; Lei Dai; Yanping Wang; Lidong Shen; Bo Shang; Yang Ji; Zhaozhong Feng (Applied Soil Ecology, 2026)

γ-aminobutyric acid (GABA) treatment alleviates off-flavor in postharvest waxed citrus fruit by enhancing peel gas permeance - Zhiquan Wang; Junchao Wang; Lu Qin; Zhen Huang; Xinxin Xu; Zhifeng Zhu; Jingjie Tang; Xiaojie Cui; Rangwei Xu; Feng Zhu; Yanping Fu; Xiuxin Deng; et al. (Postharvest Biology and Technology, 2026)

Cooling load forecasting for urban district cooling systems using a hybrid multi-scale deep learning approach - Chao Zeng; Yang Feng; Haixia Cao; Jing Wang; Yanping Yuan (Energy and Buildings, 2026)

Erastin-sensitive VDAC2 contributes to time-course peritoneal fibrosis via ferroptosis signaling induction - Wenfeng Wei; Yanping Qiu; Rong Luo; Yangping Feng (Molecular and Cellular Biochemistry, 2026)

Integrative transcriptomics and metabolomics analyses reveal changes in meat quality and muscle lipid metabolism in sheep supplemented with rumen-protected glucose - Yanping Liang; Jianchuan Shi; Xindong Cheng; Mengyu Feng; Dan Jiao; Xia Du; Kaixi Ji; Shoubin Hu; Qiaoxia Dong; Guo Yang (Meat Science, 2026)

Molecular dynamics evidence for bidirectional feedback between PFAS and humic acid during composting: Interaction mechanisms, conformational reorganization, and diffusion regulation - Shujie Hou; Chaoyue Zhao; Xu Li; Yanping Zhang; Bingzhen Li; Ziwei Dai; Qiyu Gong; Xinchang Zhou; Xiaolong Gao; Feng Ma; Yaonan Zhu; Fuxin Yang; et al. (Journal of Hazardous Materials, 2026)

Early thermal pulses drive interfacial pre-aging and plastisphere pre-shaping: An overlooked pre-conditioning pathway in PLA microplastic aging during composting - Yanping Zhang; Youzhao Wang; Chaoyue Zhao; Fuxin Yang; Xu Li; Shujie Hou; Bingzhen Li; Zhengnan Zhu; Ziwei Dai; Ziqian Wang; Xinchang Zhou; Qiyu Gong; et al. (Journal of Hazardous Materials, 2026)

GmHMGR6 enhances salt stress tolerance in soybean through modulation of nitrogen metabolism - Xinjie Feng; Hongzhen Liu; Yingyue Zhang; Yanping Li; Zhengxing Guo; Rong Bao; Xiuli Zhang; Xinying Liu; Huihui Zhang (Plant Cell Reports, 2026)

Corrigendum to “Thermally driven polymer disentanglement: An overlooked Key pathway in PBAT-microplastic aging during composting” [J Hazard Mater 503 (2026) 141080] - Yanping Zhang; Xu Li; Youzhao Wang; Fuxin Yang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Yang Yun; Feng Ma; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

Molecular mechanism by which high temperature and RecBCD synergistically lower strand-separation barriers and promote destabilization of representative efflux-pump ARG fragments (macB/tetA) during hyperthermophilic composting - Xu Li; Youzhao Wang; Xiaoyan Dang; Yanping Zhang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Feng Ma; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

Antagonistic modulation of myosin conformational dynamics by sanshool and smoke-derived aldehydes: A molecular basis for heterocyclic amine control in thermal processing - Hongyu Deng; Jie Jia; Lihui Feng; Siwei Xiong; Hemei Yuan; Zhiyuan Fang; Qiulan Li; Shengjie Duan; Hongkang Zhu; Ya Wang; Jun Sheng; Yanping Huang; et al. (Food Chemistry, 2026)

Defensive remodeling of gut microbiota under microplastic stress and its pathogenic mechanism - Penghua Jian; Feng Zhang; Zhihao Chen; Xuan Zhou; Yan Xiong; Qiang Hu; Yingyu Wang; Dan Li; Jiai Yan; Ju Yang; Hong Cao; Ping Wu; et al. (Chemico-Biological Interactions, 2026)

Uncovering time-lagged causal mechanisms in hyperthermophilic composting using Peter–Clark momentary conditional independence algorithm - Yanping Zhang; Youzhao Wang; Ling Zhou; Fuxin Yang; Xu Li; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Ziqian Wang; Xinchang Zhou; Qiyu Gong; et al. (Bioresource Technology, 2026)

Integrative histological and multi-omics analyses reveal hormone-driven cell regeneration mechanisms during postharvest wound healing in melon - Congcong Wang; Yanping Hu; Baibi Zhu; Jihao Chen; Feng Wang; Shiqi Lu; Min Wang (Postharvest Biology and Technology, 2026)

Influence of organosilicon spray adjuvants on the growth of maize and wheat: a comparison with exogenous silica fertilizer under drought conditions - Yanping Feng; Yuanqiang Luo; Yu Xiang; Mengting Liang; Yuanyuqing Xiao; Yuping Zhang (Cereal Research Communications, 2026)

Monoglyceride-templated interfacial crystallization modulates stability and controlled release in beeswax-based double emulsions - Zengliu Song; Yanping Huang; Xinru Shi; Tianhui Feng; Xinyue Ning; Junqin Chen; Renrun Cao; Jie Xiao (Journal of Food Engineering, 2026)

Zwitterionic nanoparticle-mediated interfacial hydration for robust, salt-rejecting, and anti-fouling solar steam generation - Jianbin Zhang; Yuhao Zhai; Zhichao Chen; Ting Lv; Dianming Li; Yanhua Liu; Yanping Wang; Wufang Yang; Baoli Ou; Libang Feng; Feng Zhou (Chemical Engineering Journal, 2026)

Dynamic Variations of Agricultural Drought and its Response to Meteorological Drought Based on a Three-Dimensional Spatiotemporal Clustering Perspective - Fei Wang; Hexin Lai; Ruyi Men; Zipeng Wang; Yanbin Li; Yunzhong Jiang; Kai Feng; Wenxian Guo; Qingqing Tian; Yanping Qu (Water Resources Management, 2026)

Component-specific microbial degradation and humification mechanisms of typical kitchen waste during winter hyperthermophilic composting in northeastern China - Youzhao Wang; Bingzhen Li; Jiacheng Li; Chaoyue Zhao; Xu Li; Yanping Zhang; Shujie Hou; Feng Ma; Ziwei Dai; Qiyu Gong; Xinchang Zhou; Fuxin Yang; et al. (Journal of Environmental Management, 2026)

Divergent responses of maize and soybean to intercropping: Insights from arbuscular mycorrhizal fungi diversity, colonization, and related-genes expression - Shihui Yu; Xinru Liu; Ling Liu; Yanping Ma; Baohong Liu; Wuyan Xiang; Ying Zhang; Peiyong Liu; Chen Feng; Caixia Sun (Plant and Soil, 2026)

Thermally driven polymer disentanglement: An overlooked Key pathway in PBAT-microplastic aging during composting - Yanping Zhang; Xu Li; Youzhao Wang; Fuxin Yang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Yang Yun; Feng Ma; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

Spatially stratified humification mechanisms in industrial-scale negative-pressure aerated thermophilic composting: Dominant pathways driven by temperature gradients and microbial succession - Shujie Hou; Youzhao Wang; Xu Li; Yanping Zhang; Xiaolong Gao; Jiedong Hao; Bingzhen Li; Ziwei Dai; Feng Ma; Fuxin Yang; Chaoyue Zhao; Tong Zhu (Journal of Environmental Chemical Engineering, 2026)

High-resolution skin-like microlithographic displays for visual-tactile system - Baoying Sun; Xiaoli Zhao; Chuang Xue; Mingxin Zhang; Pengbo Xi; Guoqiang Ren; Hao Liu; Junru Zhang; Yanping Ni; Yanhong Tong; Liangwen Feng; Qingxin Tang; et al. (Chemical Engineering Journal, 2026)

Pou4f3 Deficiency Obstructs the Subtype Differentiation of Vestibular Hair Cells - Qin Zhou; Yikang Huang; Wenli Ni; Mingchuan Feng; Lingjie Wu; Chuijin Lai; Yanping Zhang; Wenyan Li; Yan Chen (Neuroscience Bulletin, 2026)

Grass roots on gully bed inhibit plunge pool development but have a limited influence on headcut retreat: a case study based on an in-situ experiment in dry-hot valley of southwest China - Yanping Liu; Yifan Dong; Jie Feng; Ronghua Zhong; Li Rong (CATENA, 2026)

Stage-specific bacterial-fungal synergy in industrial-scale hyperthermophilic composting: Community assembly dynamics and modular networks drive humification - Chaoyue Zhao; Youzhao Wang; Feng Ma; Xu Li; Yanping Zhang; Shujie Hou; Bingzhen Li; Xiaodan Zhang; Fuxin Yang; Liying Hao; Tong Zhu (Journal of Environmental Management, 2025)

Metabolic basis of resveratrol biosynthesis in P. megaterium PH3: Key roles of phenylpropanoid precursors and enzymatic feedback inhibition - Xiaohan Zhang; Dong Zhang; Junbo Liang; Liang Wang; Yanping Cui; Dingding Feng; Shuhong Ye (Food Chemistry, 2025)

The rhizosphere as a hotspot for nitrite- and nitrate-dependent anaerobic oxidation of methane in paddy fields - Yanping Wang; Yanan Bai; Lidong Shen; Bo Shang; Yang Ji; Xupeng Miao; Bingjie Ren; Yuling Yang; Wangting Yang; Zhaozhong Feng (Environmental Pollution, 2025)

Selenium-doped NiCo2O4 drives nanozyme innovation: new ideas in water disinfection - Yanping Feng; Zizhuo Liu; Kexin Zhang; Fanyan Deng; Congqin Ning (Journal of Cleaner Production, 2025)

Impact of microplastics on plant biogenic volatile organic compounds emission: A preliminary study - Shuqin Liu; Shengmei Feng; Yanping Zhang; Yang Zheng; Ruifen Jiang; Gangfeng Ouyang (Journal of Hazardous Materials, 2025)

W2O6/CoFe2O4: An efficient catalyst to activate peroxymonosulfate for the elimination of antibiotic-resistant bacteria and genes in aquaculture effluent - Yanqiong Zhang; Muting Yan; Gaoling Wei; Fengru Lu; Feng Li; Peng Liu; Yanping Zhu; Han Gong (Journal of Environmental Chemical Engineering, 2025)

Montmorillonite-enhanced Carboxymethylcellulose/Polyethyleneimine aerogel: A highly efficient and reusable adsorbent for caffeine removal from tea infusions - Wenyue Yu; Yangyu Zhou; Ya Liu; Huan Guo; Lihui Huang; Lu Feng; Jinrong Bai; Yue Xiao; Yanping Wu; Kai Zhong; Yina Huang; Hong Gao (Food Chemistry, 2025)

Prenatal high-sucrose diet affects pulmonary artery contractile functions via MT receptors - Xueqin Feng; Hongwei Fu; Xiao Sun; Hua Shu; Yongning Zhu; Yanyan Bai; Qinggui Ren; Xinying Liu; Meng Liu; Fanyong Zhang; Yanping Wang (Reproductive Toxicology, 2025)

Enhancing humification in high-temperature composting: Insights from endogenous and exogenous heating strategies - Chaoyue Zhao; Feng Ma; Youzhao Wang; Xu Li; Yanping Zhang; Zhipeng Wang; Wei Xiong; Xiaolong Gao; Yongguang Ma; Fuxin Yang; Tong Zhu (Bioresource Technology, 2025)

A 3D self-floating evaporator loaded with phase change energy storage materials for all-weather desalination - Yuqin Teng; Shuai Li; Yanxia Luo; Xin Yi; Libang Feng; Dianming Li; Yanping Wang (Desalination, 2024)

Construction of structure-matching In-Ni catalysts for the selective hydrogenation of α-methylacrolein - Lin Ai; Yanping Chen; Fang Lu; Jiaxu Liu; Xiao-Feng Wu; Shengjun Huang (Chemical Engineering Journal, 2024)

Salidroside Reduced Ca2+-CaM-CAMKII-Dependent eNOS/NO Activation to Decrease Endothelial Cell Injury Induced by Cold Combined with Hypoxia - Hongjin Wang; Xianzhen Wang; Yanping Feng; Kewei Zhang; Maodongzhi Peng; Xiaowei Wu; Yi Li (Cell Biochemistry and Biophysics, 2024)

Uncovering the Shuixian tea grades hierarchy in Chinese national standard: From sensory evaluation to microstructure and volatile compounds analysis - Yanping Lin; Yibiao Huang; Xia Liu; Yani Pan; Xinyu Feng; Haowei Guo; Xiaolan Li; Yike Tao; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Multi-drug loaded electrospinning nanofibers promote healing with less scar formation by remodeling wound microenvironment via modulating TGF-β1/Smads/EN1 signal - Xiaoyan Zeng; Zhenfeng Guan; Reyisha Yusufu; Siyi Li; Qi WU; Yanping Feng; Tiantian Chen; Muxiang Luo; Fenghuan Wei (Chemical Engineering Journal, 2024)

Two-stage hydrothermal liquefaction of Spirulina: Experimental observations, energy analysis and techno-economic assessment - Hongwei Pang; Yanping Feng; Xinru Ma; Qirong Yang; Zhaoying Li (Process Safety and Environmental Protection, 2024)

Adsorption mechanism and remediation of heavy metals from soil amended with hyperthermophilic composting products: Exploration of waste utilization - Feng Ma; Tong Zhu; Youzhao Wang; Shuichi Torii; Zhipeng Wang; Chaoyue Zhao; Xu Li; Yanping Zhang; Haoyu Quan; Chunli Yuan; Liying Hao (Bioresource Technology, 2024)

Effective strategy for Cr(VI) removal from water in evolution process of ferroan brucite by redox and intercalation - Shifeng Zhao; Fengzhu Lv; Yanping Zhao; Jiajing Feng; Hanxia Tang (Journal of Water Process Engineering, 2024)

Dynamic relationships and propagation characteristics between meteorological drought and vegetation drought based on a three-dimensional identification algorithm - Fei Wang; Hexin Lai; Zipeng Wang; Ruyi Men; Yanbin Li; Yunzhong Jiang; Kai Feng; Qingqing Tian; Xuefang Du; Yanping Qu (Global and Planetary Change, 2024)

A highly sensitive SERS substrate of porous membrane-Ag NPs for kidney cancer detection - Sheng Chen; Jiamin Gao; Hongyi Zhang; Li Liu; Feng Lin; Zaijun Cheng; Yanping Chen; Dongyu Guo; Xingen Gao; Juqiang Lin (Analytica Chimica Acta, 2024)

Community Structure Characteristics and Changes in Fish Species at Poyang Lake after the Yangtze River Fishing Ban - Yanping Zhang; Haixin Zhang; Zijun Wu; Mingguang Zhao; Guangpeng Feng (Fishes, 2024)
To understand the fish community structure characteristics and changes in Poyang Lake after the Yangtze River fishing ban in 2021, seven sampling stations were established, namely in Hukou, Lushan, Duchang, Yongxiu, Nanjishan, Ruihong, and Poyang, for fishery resource surveys between 2020 and 2021. The results showed that 93 fish species were identified, belonging to 11 orders, 20 families, and 61 genera, which was an increase of 4.5% from before the fishing ban. Of these, 52 Cyprinidae species were identified, comprising the highest proportion (55.91%). Four invasive alien species (hybrid sturgeon, Cirrhina mrigala, Piaractus brachypomus, and Mugil cephalus) were identified, and the number of alien species in Poyang Lake was higher than before the fishing ban. Carnivorous and mid-lower-level fish showed a significant increase, accounting for 47.31% and 38.71% of the total species, respectively. Compared with the Yangtze River before the fishing ban, the body length and body weight of the main economic fish in Poyang Lake increased by 6.10–61.26% and by 15.14–291.57%, respectively. In terms of age structure, the proportion of major economically important fish aged 1 or 2 years decreased significantly, while the proportion of older fish increased substantially. There was little difference in the diversity of fish communities at different stations in Poyang Lake. In terms of biodiversity, the Shannon–Wiener index ranged from 2.158 to 2.909, with Poyang having the highest value and Nanjishan the lowest. Margalef’s index ranged from 4.265 to 6.459, with Lushan having the highest value and Nanjishan the lowest. Pielou’s index ranged from 0.617 to 0.822, with Duchang having the highest value and Nanjishan the lowest. Hence, the Yangtze river fishing ban has played an important and positive role in the restoration of fishery resources in Poyang Lake. However, long-term tracking and monitoring are needed to provide information to comprehensively evaluate the ecological impact of the Poyang Lake fishing ban.

A newly-discovered tea population variety processed Bai Mu Dan white tea: Flavor characteristics and chemical basis - Yanping Lin; Yibiao Huang; Su Zhou; Xiaolan Li; Yike Tao; Yani Pan; Xinyu Feng; Haowei Guo; Ping Chen; Qiang Chu (Food Chemistry, 2024)

Unlocking the potential of biochar: an iron-phosphorus-based composite modified adsorbent for adsorption of Pb(II) and Cd(II) in aqueous environments and response surface optimization of adsorption conditions - Xu Li; Yuan Chi; Feng Ma; Xiaoxin Wang; Rui Du; Zhipeng Wang; Xiaoyan Dang; Chaoyue Zhao; Yanping Zhang; Shumin He; Youzhao Wang; Tong Zhu (Environmental Science and Pollution Research, 2024)

Universal patterns and differences in graded aggressive calls of greater horseshoe bats from distant populations - Kangkang Zhang; Yanping Yu; Tong Liu; Jianan Ding; Hao Gu; Jiang Feng; Ying Liu (Animal Behaviour, 2024)

Identification and characterization of Achromobacter spanius P-9 and elucidation of its deoxynivalenol-degrading potential - Feng Yao; Yaowen Du; Siyi Tian; Guoli Chang; Yanping Zhang; Ruiyu Zhu; Chenggang Cai; Suqin Shao; Ting Zhou (Archives of Microbiology, 2024)

Aralianudaside A, an unusual skeleton triterpenoid saponin with anti-airway inflammatory activity from Aralia elata - Pengcheng Yin; Haishan Qian; Shaohua Li; Benqin Tang; Juan Wang; Shuai Chen; Guanghui Ni; Fawu Dong; Yanping Li; Feng Huang; Rongping Zhang; Hongping He; et al. (Natural Product Research, 2024)

Rational design and fabricate of protonated crosslinked chitosan adsorbent for boosting the removal of nitrite in water - Wenbin Chen; Yanping Feng; Xiaoming Wang; Chenchen Zhang; Suyao Liu; Yibing Song; Yiwen Fang (Chemical Engineering Journal, 2024)

Equal importance of humic acids and nitrate in driving anaerobic oxidation of methane in paddy soils - Yanan Bai; Yanping Wang; Lidong Shen; Bo Shang; Yang Ji; Bingjie Ren; Wangting Yang; Yuling Yang; Zhiguo Ma; Zhaozhong Feng (Science of The Total Environment, 2024)

Strategies for deoxynivalenol (DON) degradation by microbes from organic fertilizers and influence of the bacterial diversity after DON treatment - Feng Yao; Yaowen Du; Siyi Tian; Guoli Chang; Yanping Zhang; Chenggang Cai; Ruiyu Zhu; Suqin Shao; Ting Zhou (International Biodeterioration & Biodegradation, 2024)

Seismic response of a mid-story isolated structure considering SSI in mountainous areas under long-period earthquakes - Feng Wan; Shengwu Qin; Dewen Liu; Tiange Zhao; Yanping Zheng; Hang Shan; Zhiang Li; Fusong Peng; Jingran Xu; Min Lei (Earthquake Engineering and Engineering Vibration, 2024)

Multi-omics analysis of oxidative stress and apoptosis in hepatopancreas cells induced by Polyascus gregaria parasitizing the Eriocheir sinensis - Shiwei Zhao; Qingbiao Hu; Hongbo Jiang; Yingying Zhao; Yanping Wang; Chengcheng Feng; Xiaodong Li (Fish & Shellfish Immunology, 2023)

Effects of supplementary thyme on immunity responses, antioxidant indices, rumen enzymes concentrations and rumen bacteria composition in Hu sheep - Xia Du; Xindong Cheng; Kaixi Ji; Abraham Allan Degen; Yanping Liang; Xiukun Wu; Qiaoxia Dong; Mengyu Feng; Dan Jiao; Haitao Cong; Guo Yang (Animal Feed Science and Technology, 2023)

Drought characteristics and dominant factors across China: Insights from high-resolution daily SPEI dataset between 1979 and 2018 - Lingling Wan; Virgílio A. Bento; Yanping Qu; Jianxiu Qiu; Hongquan Song; RongRong Zhang; Xiaoping Wu; Feng Xu; Jinkuo Lu; Qianfeng Wang (Science of The Total Environment, 2023)

Spatio-temporal evolution and teleconnection factor analysis of groundwater drought based on the GRACE mascon model in the Yellow River Basin - Fei Wang; Hexin Lai; Yanbin Li; Kai Feng; Qingqing Tian; Wenxian Guo; Yanping Qu; Haibo Yang (Journal of Hydrology, 2023)

Effect of oligosaccharides as lyoprotectants on the stability of curcumin-loaded nanoliposomes during lyophilization - Hanyun Jiang; Yanping Wang; Xiankang Xu; Leiyu Deng; Lifang Feng; Jianzhong Han; Weilin Liu (Food Chemistry, 2023)

Molecular cloning, functional characterization and expression of the β-amyrin synthase gene involved in saikosaponin biosynthesis in Bupleurum chinense DC. - Yanping Mao; Hua Chen; Jun Zhao; Yuchan Li; Liang Feng; Yuping Yang; Yiguan Zhang; Ping Wei; Dabin Hou (Journal of Plant Biochemistry and Biotechnology, 2023)

Fcγ receptor‐mediated phagocytosis pathway was involved in phagocytosis of mIgM + B lymphocytes from largemouth bass ( Micropterus salmoides ) - Jing Wu; Yifan Nie; Jingya Wang; Guoqing Feng; Le Hao; Yanping Ma; Yugu Li; Zhenxing Liu (Journal of Fish Biology, 2023)
The potential for phagocytosis has been proven in teleost B cells, but the research on the regulatory mechanism of phagocytosis remains lacking. In this study, three largemouth bass ( Micropterus salmoides ) (15 ± 5 g) were injected intraperitoneally with Nocardia seriolae (10 5 CFU/100 μl/fish) in vivo , and their spleen was collected at 72 h post‐infection for mRNA‐seq. After the de novo assembly of the paired‐end reads, 73,622 unigenes were obtained. Gene expression profiling revealed that 2043 unigenes were differentially expressed after N. seriolae infection, comprising 1285 upregulated and 758 downregulated unigenes ( q ‐value 0.05, log2FC > |2|) of which 181 genes were involved in phagocytosis. The Kyoto Encyclopaedia of Genes and Genomes (KEGG) analysis demonstrated that 12 differentially expressed genes (DEG) associated with phagocytosis were enriched in the Fcγ receptor‐mediated phagocytosis signalling pathway. In vitro , the phagocytic ability of mIgM + B lymphocytes was validated using indirect immunofluorescence assay (IIFA) and fluorescence activating cell sorter (FACS), and the phagocytosis rates of the mIgM + B lymphocytes incubated with a Lyn inhibitor had decreased from 18.533 ± 6.00% to 11.610 ± 4.236% compared with the unblocked group. These results suggested that the Fcγ receptor‐mediated phagocytosis signalling pathway had participated in the phagocytosis of B cells and provide further insight into the role of B cells in innate immunology.

Host adaptation of codon usage in SARS-CoV-2 from mammals indicates potential natural selection and viral fitness - Yanan Fu; Yanping Huang; Jingjing Rao; Feng Zeng; Ruiping Yang; Huabing Tan; Zhixin Liu; Weixing Du; Long Liu (Archives of Virology, 2022)

Novel genome sequence of Chinese cavefish ( Triplophysa rosa ) reveals pervasive relaxation of natural selection in cavefish genomes - Qingyuan Zhao; Feng Shao; Yanping Li; Soojin V. Yi; Zuogang Peng (Molecular Ecology, 2022)
All cavefishes, living exclusively in caves across the globe, exhibit similar phenotypic traits, including the characteristic loss of eyes. To understand whether such phenotypic convergence shares similar genomic bases, here we investigated genome‐wide evolutionary signatures of cavefish phenotypes by comparing whole‐genome sequences of three pairs of cavefishes and their surface fish relatives. Notably, we newly sequenced and generated a whole‐genome assembly of the Chinese cavefish Triplophysa rosa . Our comparative analyses revealed several shared features of cavefish genome evolution. Cavefishes had lower mutation rates than their surface fish relatives. In contrast, the ratio of nonsynonymous to synonymous substitutions ( ω ) was significantly elevated in cavefishes compared to in surface fishes, consistent with the relaxation of purifying selection. In addition, cavefish genomes had an increased mutational load, including mutations that alter protein hydrophobicity profiles, which were considered harmful. Interestingly, however, we found no overlap in positively selected genes among different cavefish lineages, indicating that the phenotypic convergence in cavefishes was not caused by positive selection of the same sets of genes. Analyses of previously identified candidate genes associated with cave phenotypes supported this conclusion. Genes belonging to the lipid metabolism functional ontology were under relaxed purifying selection in all cavefish genomes, which may be associated with the nutrient‐poor habitat of cavefishes. Our work reveals previously uncharacterized patterns of cavefish genome evolution and provides comparative insights into the evolution of cave‐associated phenotypic traits.

Occurrence of polycyclic aromatic hydrocarbons (PAHs) in the seafood from an important fishing area in the East China Sea and a comparison between seafood from different origins - Wang Qian; Lu Dequan; Xiong Yiran; Peng Fei; Li Juan-ying; Wu Feng; Chu Yanping; Sun Ruihua; Tian Siquan (Environmental Monitoring and Assessment, 2022)

Poor evidence for host-dependent regular RNA editing in the transcriptome of SARS-CoV-2 - Jinbao Zong; Yanping Zhang; Fenfen Guo; Changyuan Wang; Hong Li; Gaoyang Lin; Wenqing Jiang; Xiaoping Song; Xiufang Zhang; Feng Huang; Min Qi; Xin Zheng (Journal of Applied Genetics, 2022)

Localization and regulatory function of Yin Yang 1 (YY1) in chicken testis - Ligen Chen; Lingyun Qiao; Yan Guo; Ying Huang; Wei Luo; Yanping Feng (Molecular Genetics and Genomics, 2022)

Differential effects of three amendments on the immobilisation of cadmium and lead for Triticum aestivum grown on polluted soil - Shengze Zhang; Lingtong Quan; Yanping Zhu; Jin Yan; Xiaoman He; Jia Zhang; Xiaoming Xu; Zhubing Hu; Feng Hu; Yahua Chen; Zhenguo Shen; Yan Xia (Environmental Science and Pollution Research, 2020)

High plant species richness and stable climate lead to richer but phylogenetically and functionally clustered avifaunas - Na Wang; Lingfeng Mao; Xueting Yang; Xingfeng Si; Yanping Wang; Wolf L. Eiserhardt; Gang Feng (Journal of Biogeography, 2020)
Aims Glacial–interglacial climate stability and contemporary climate could affect bird diversity through their direct effects on diversification and physiological tolerance, and indirect effects on plant species richness, which could provide more food and ecological niches. This study aims to quantitatively assess the direct and indirect effects of these drivers on species richness, phylogenetic and functional structure of bird assemblages. Location Mainland China. Taxon Birds. Methods Ordinary least squares models and simultaneous autoregressive models were used to test the associations between glacial–interglacial climate anomaly, contemporary climate, plant species richness, elevation range and species richness, phylogenetic structure, functional structure of bird assemblages in mainland China. Structural equation models were used to distinguish between direct and indirect effects of these variables on bird diversity. Results High bird species richness with phylogenetically and functionally clustered structure occurred in regions with more plant species and stable glacial–interglacial climate. Notably, the phylogenetically clustered bird assemblages were composed of young lineages. Contemporary precipitation and elevation range affected bird diversity through their indirect effects on plant species richness. Main Conclusions These findings suggest that more plant species and stable glacial–interglacial climate may promote bird diversity through their effects on in situ diversification and species dispersal rate in southwestern China. Therefore, the well‐preserved plant and bird diversity through the long‐term climate fluctuations should be of great importance of biodiversity conservation in China.

Silica colloids as non-carriers facilitate Pb2+ transport in saturated porous media under a weak adsorption condition: effects of Pb2+ concentrations - Chaomeng Dai; Hui Zhou; Xueji You; Yanping Duan; Yaojen Tu; Shuguang Liu; Feng Zhou; Leong Kah Hon (Environmental Science and Pollution Research, 2020)

Characterizing the effects of hypoxia on the metabolic profiles of mesenchymal stromal cells derived from three tissue sources using chemical isotope labeling liquid chromatography-mass spectrometry - Qiaoling Pan; Dan Wang; Deying Chen; Yanni Sun; Xudong Feng; Xiaowei Shi; Yanping Xu; Xian Luo; Jiong Yu; Yang Li; Hongcui Cao; Liang Li (Cell and Tissue Research, 2020)

Three-dimensional reconstruction of Picea wilsonii Mast. pollen grains using automated electron microscopy - Weiwei Shen; Lingyu Ma; Xi Zhang; Xixia Li; Yuanyuan Zhao; Yanping Jing; Yun Feng; Xueke Tan; Fei Sun; Jinxing Lin (Science China Life Sciences, 2020)

TiO2 and SiO2 Nanoparticles Combined with Surfactants Mitigate the Toxicity of Cd2+ to Wheat Seedlings - Chaomeng Dai; Hui Shen; Yanping Duan; Shuguang Liu; Feng Zhou; Deli Wu; Guihui Zhong; Akbar Javadi; Yao-Jen Tu (Water, Air, & Soil Pollution, 2019)

Identification and molecular characterization of Serratia marcescens phages vB_SmaA_2050H1 and vB_SmaM_2050HW - Changyu Tian; Jiangtao Zhao; Zheng Zhang; Xiao Chen; Xiao Wei; Huan Li; Weishi Lin; Yuehua Ke; Lingfei Hu; Aimin Jiang; Ruo Feng; Wenhui Yang; et al. (Archives of Virology, 2019)

Synthesis and biological evaluation of novel anti-hepatitis C virus (HCV) agents: 2-hydroxylphenethyl sulfanyl-oxopyrimidines - Daochun Wu; Yue Feng; Hua Wang; Junfeng Yang; Xian Chen; Yueping Wang; Christopher Cong Lai; Yufang Zhang; Cong Li; Xueshan Xia; Yanping He (Medicinal Chemistry Research, 2017)

Improving N management through intercropping alleviates the inhibitory effect of mineral N on nodulation in pea - Falong Hu; Cai Zhao; Fuxue Feng; Qiang Chai; Yanping Mu; Yan Zhang (Plant and Soil, 2017)

Effects of organic matter content and composition on ammonium adsorption in lake sediments - Li Zhang; Shengrui Wang; Lixin Jiao; Yanping Li; Jiachun Yang; Rui Zhang; Shuang Feng; Juan Wang (Environmental Science and Pollution Research, 2016)

QTL mapping for flowering time in different latitude in soybean - Sijia Lu; Ying Li; Jialin Wang; Peerasak Srinives; Haiyang Nan; Dong Cao; Yanping Wang; Jinliang Li; Xiaoming Li; Chao Fang; Xinyi Shi; Xiaohui Yuan; et al. (Euphytica, 2015)

Inhibition of the Activation and Recruitment of Microglia-Like Cells Protects Against Neomycin-Induced Ototoxicity - Shan Sun; Huiqian Yu; Hui Yu; Mei Honglin; Wenli Ni; Yanping Zhang; Luo Guo; Yingzi He; Zhen Xue; Yusu Ni; Jin Li; Yi Feng; et al. (Molecular Neurobiology, 2015)

Molecular cloning, expression profile, polymorphism and the genetic effects of the dopamine D1 receptor gene on duck reproductive traits - Cui Wang; Shijun Li; Chuang Li; Yanping Feng; Xiuli Peng; Yanzhang Gong (Molecular Biology Reports, 2012)

Genomic Differences Between Actinobacillus pleuropneumoniae Serotypes 5b and 3 and their Distribution and Transcription Among 15 Serotypes - Feng Yang; Fang Xie; Yuwen Jiang; Suqing Li; Yanping Xing; Yu Wang; Xin Feng; Wenyu Han; Liancheng Lei (Current Microbiology, 2011)

Study on gastric cancer blood plasma based on surface-enhanced Raman spectroscopy combined with multivariate analysis - ShangYuan Feng; JianJi Pan; YanAn Wu; Duo Lin; YanPing Chen; GangQin Xi; JuQiang Lin; Rong Chen (Science China Life Sciences, 2011)

Single nucleotide polymorphism of FSHβ gene associated with reproductive traits in Japanese flounder (Paralichthys olivaceus) - Feng He; Haishen Wen; Dahui Yu; Jifang Li; Bao Shi; Caifang Chen; Jiaren Zhang; Guoxiong Jin; Xiaoyan Chen; Dan Shi; Yanping Yang (Journal of Ocean University of China, 2010)

Brief report: a new profile of terminal N-acetyllactosamines glycans on pig red blood cells and different expression of α-galactose on Sika deer red blood cells and nucleated cells - Yingxia Tan; Feng Gong; Subo Li; Shouping Ji; Yanping Lu; Hongwei Gao; Hua Xu; Yangpei Zhang (Glycoconjugate Journal, 2010)

Overexpression of SBPase enhances photosynthesis against high temperature stress in transgenic rice plants - Lingling Feng; Kun Wang; Yang Li; Yanping Tan; Jin Kong; Hui Li; Yangsheng Li; Yingguo Zhu (Plant Cell Reports, 2007)